Impact of bio-stimulants on growth, flowering, fruit quality and yield parameters of brinjal (Solanum melongena L.) - Chaitra, A J; Mallikarjuna Gowda, A P; Srinivasappa, K N; kavita, Kandpal; Manjunath, B (Plant Science Today, 2026)
Bio-stimulants have emerged as innovative, eco-friendly solutions representing a paradigm shift toward sustainable agricultural production systems. A field experiment conducted at Zonal Agricultural Research Station, GKVK, Bengaluru over two rabi seasons (2023 and 2024) evaluated the effect of soil and foliar applications of bio-stimulant on growth, flowering, fruit quality and yield of brinjal (Solanum melongena L.). The treatments included: Control (T1 ), soil application of sea weed extract 5 mL/L (T2 ), soil application of chitosan 20 mL/L (T3) soil application of humic acid 4 mL/L (T4), soil application of amino acid 3 mL/L (T5), soil application of arka microbial consortium 10 mL/L (T6 ), foliar application of sea weed extract 5 mL/L (T7 ), foliar application of chitosan 20 mL/L (T8 ), foliar application of humic acid 4 mL/L (T9) foliar application of amino acid 3 mL/L (T10) and foliar application of arka microbial consortium 10 mL/L (T11) was applied on 15, 30, 45 and 60 days after transplanting. Foliar application of seaweed extract (T₇) consistently produced the highest plant height (82.07 cm), primary branches (8.58), number of leaves (57.74) and shortest days to first flowering (43.25 days) and 50 % flowering (51.15 days). T7 also recorded the maximum fruit number, fruit size and yield, with pooled yield increasing to 15.56 t ha-1 relative to 11.90 t ha-1 in the control. Foliar applications performed better than corresponding soil applications across treatments. The findings indicate that seaweed extract applied as a foliar spray is an effective bio-stimulants for enhancing brinjal productivity under field conditions. These findings demonstrate that seaweed extract foliar spray is an effective, economically viable bio-stimulant for sustainable agriculture production.